2016
DOI: 10.3389/fpls.2016.01703
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Hevea brasiliensis ErbB-3 Binding protein 1 Gene Increases Drought Tolerance and Organ Size in Arabidopsis

Abstract: Rubber trees are economically important tropical tree species and the major source of natural rubber, which is an essential industrial material. This tropical perennial tree is susceptible to cold stress and other abiotic stresses, especially in the marginal northern tropics. Recent years, the genome sequencing and RNA-seq projects produced huge amount of sequence data, which greatly facilitated the functional genomics study. However, the characterization of individual functional gene is in urgent demands, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…The organ size of plants is related to cellular processes, such as cell proliferation and expansion (Horváth et al, 2006;Du et al, 2014;Cheng et al, 2016). The expression of MSI4 was up-regulated in TsNAC1 OX lines, and Arabidopsis MSI4 mutants showed a severalfold increase in vegetative biomass and a 1.3-fold expansion in cell size (Morel et al, 2009).…”
Section: Tsnac1 Retards Growth By Restricting Cell Expansion and Orgamentioning
confidence: 99%
“…The organ size of plants is related to cellular processes, such as cell proliferation and expansion (Horváth et al, 2006;Du et al, 2014;Cheng et al, 2016). The expression of MSI4 was up-regulated in TsNAC1 OX lines, and Arabidopsis MSI4 mutants showed a severalfold increase in vegetative biomass and a 1.3-fold expansion in cell size (Morel et al, 2009).…”
Section: Tsnac1 Retards Growth By Restricting Cell Expansion and Orgamentioning
confidence: 99%
“…This antagonism suggested that EBP1 provides an important link between a growth driver and cell cycle regulation (Horváth et al, 2006). The initial finding that EBP1 enhances growth was verified for a number of EBP1 orthologs identified in different species (Cao et al, 2009;Cheng et al, 2016;Wang et al, 2016); however, another report described an opposite effect (Li et al, 2016). Additionally, EBP1 expression is induced upon abiotic stress, and when EPB1 levels are elevated, it can confer stress tolerance (Cao et al, 2009;Cheng et al, 2016).…”
mentioning
confidence: 97%
“…To construct the RNA-Seq cDNA library, total RNA was extracted from 2-week-old dark-grown seedlings as previously described (Cheng, Chen, Zhu, & Huang, 2016). Six Illumina cDNA libraries were prepared using the Illumina TruSeq RNA sample preparation kit following the manufacturer's instructions.…”
Section: Rna-seq and Bioinformatic Analysismentioning
confidence: 99%